<---- Sponsored ads ------ >

Solve, 5x2 + 11x + 6 = 0


Solution.

Given equation is 5x2 + 11x + 6 = 0

Comparing it with the standard Form of Quadratic Equation ax2 + bx + c = 0

a = 5, b = 11, c = 6

As we know, discriminant = b2 - 4ac

Discriminant = (11)2 - 4(5)(6)

Discriminant = 121 - (120)

Discriminant = 1

Since discriminant > 0
Both roots are real and unequal.

Using quadratic formula


Roots(x1, x2) = −b ± √   b2 − 4ac 
         2a          


Roots(x1, x2) = −b ± √ D
         2a          


x1 = −b + √D
         2a          


=   −(11) + √1
         2(5)          


=    -11 + 1
         10          


= -1


x2 = −b - √D
         2a          


=   −(11) - √1
         2(5)          


=    -11 - 1
         10          


=    -12
   10    


Roots: x1 = ,     x2 =


Sum of roots = -b/a

Sum of roots = -(11)/(5)

Sum of roots = -2.2


Product of roots = c/a

Product of roots = (6)/(5)

Product of roots = 6 / 5
<---- Sponsored ads ----- >

© 2020-2030 Amibba Systems Private Limited. All rights reserved.